PENGEMBANGAN BAHAN AJAR HAND OUT BERBASIS KODE QR DALAM MATERI PENGUMPULAN DATA KELAS V MADRASAH IBTIDAIYAH - Chikmah, Lailatul; Azhari, Azhari; Malik, Muh Syauqi (Prodi PGMI STIT Sunan Giri Bima, 2023)
Mathematics is a fundamental science; its scientific results cannot be revised or written because it follows mathematical proof. This creates anxiety and problems from various facts that exist for students, making their learning outcomes decrease. Moreover, rapid technological advances are not balanced with advances in the quality of existing human resources coupled with the COVID-19 pandemic, which significantly affects the world of education in Indonesia, and the intellectual quality of students is declining. With the advancement of technology, it should be an opportunity to develop teaching material to make it easier for students to carry out teaching and learning activities. The development of teaching materials that will be discussed in this article is the development of QR code-based handout teaching materials containing learning videos that are relevant to the material studied, namely, grade 5 material in the form of data collection.